Interpretation of the composition of trioctahedral micas - Foster, Margaret Dorothy, 1895- (Professional paper (Geological Survey (U.S.)), 1960)
"A study of the compositional and layer charge relations of phlogopites, biotites, siderophyllites and lepidomelanes."